Influence of melt overheating treatment on solidification behavior of BiTe-based alloys at different cooling rates. (25th December 2015) - Yu, Yuan; Lv, Long; Wang, Xiao-yu; Zhu, Bin; Huang, Zhong-yue; Zu, Fang-qiu
Abstract: Persistent efforts have been made to improve the performance of thermoelectric (TE) materials by different preparation methods. However, scarce attention has been paid to the effects of liquid state on solidified structures and properties of TE materials. In this work, the abnormal resistivity-temperature (ρ – T) behaviors of Bi2 Te3 and Bi0.5 Sb1.5 Te3 melts during a definite temperature range in the first heating process were observed, which implied a temperature-induced liquid–liquid structural transition (TI-LLST) may exist in the liquid alloys. Based on this information, by melting specimens at different temperatures before and after TI-LLST and then solidifying at various cooling rates, it is found that the microstructures of solidified specimens are refined and the hardness elevate with cooling rate increasing for a specific composition. More significantly, the effects of crystal size decreasing and hardness increasing are further optimized by melt overheating treatment. In addition, this technique can also alter the crystallographic preferred orientation in some degree, which can also influence the transport of electrons and phonons. Since the TE and mechanical properties are highly susceptible to microstructures, the present work may provide an alternative approach to adjust the performance of TE materials and to improve the reliability and sustainability of TE devices in service. Graphical abstract: Highlights: Temperature-induced liquid–liquid structure transition exists in BiTe-based alloy. Solidified structures are refined with cooling rate increasing. Hardness is elevated with cooling rate increasing. Both structures and hardness are further optimized by melt overheating treatment.